Electrochemical, spectroelectrochemical and surface photovoltage study of ambipolar C60-EDOT and C60-Carbazole based conducting polymers. (10th July 2019) - Heredia, Daniel A.; Gonzalez Lopez, Edwin J.; Durantini, Edgardo N.; Durantini, Javier; Dittrich, Thomas; Rappich, Jörg; Macor, Lorena; Solis, Claudia; Morales, Gustavo M.; Gervaldo, Miguel; Otero, Luis
Abstract: Ethylenedioxythiophene (EDOT) and Carbazole (CBZ) based conducting polymers holding pendant C60 Buckminster fullerene were formed by electrochemical induced dimerization of four structurally related monomers. Electrochemical and spectroelectrochemical characterization of the thin films clearly indicates the presence of EDOT and CBZ dimers as structural building blocks of the polymeric materials. Under positive applied potentials, all the synthesized conductive materials generate UV–visible-near IR absorption bands that denote the presence of two oxidized states in the electrochemical generated dimers. Also, the four polymeric films showed reversible reduction of the C60 units. The capacity of the materials for the production of photoelectric effects was analyzed by surface photovoltage spectroscopy, showing that the illumination of C60 -CBZ polymers causes preferential separation of photogenerated charge carriers in the double-cable polymeric organic films. Graphical abstract: Image 1 Highlights: Four C60 -based donor-acceptor monomers are electropolymerized on Pt and ITO. The polymers can oxidized and reduced as part of an ambipolar structure. The presence of EDOT or DCBZ dimers in the polymer structures is confirmed. Photoinduced charge separation and charge migration are observed in the films. Photovoltage spectra fully match the absorption spectra of the polymeric films.